Parallel Reaction Monitoring Mass Spectrometry for Rapid and Accurate Identification of β-Lactamases Produced by Enterobacteriaceae - Lu, Yun; Hu, Xinxin; Pang, Jing; Wang, Xiukun; Li, Guoqing; Li, Congran; Yang, Xinyi; You, Xuefu (Frontiers in Microbiology, 2022)
The increasing spread of drug-resistant bacterial strains presents great challenges to clinical antibacterial treatment and public health, particularly with regard to β-lactamase-producing Enterobacteriaceae. A rapid and accurate detection method that can expedite precise clinical diagnostics and rational administration of antibiotics is urgently needed. Targeted proteomics, a technique involving selected reaction monitoring or multiple reaction monitoring, has been developed for detecting specific peptides. In the present study, a rapid single-colony-processing procedure combined with an improved parallel reaction monitoring (PRM) workflow based on HRAM Orbitrap MS was developed to detect carbapenemases (Klebsiella pneumoniae carbapenemase, KPC; imipenemase, IMP; Verona integron-encoded metallo-β-lactamase, VIM; New Delhi metallo-β-lactamase, NDM; and oxacillinase, OXA), extended spectrum β-lactamases (TEM and CTX-M), and AmpC (CMY-2) produced by Enterobacteriaceae. Specific peptides were selected and validated, and their coefficients of variation and stability were evaluated. In total, 188 Enterobacteriaceae strains were screened using the workflow. 14 out of total 19 peptides have 100% specificity; 3 peptides have specificity >95% and 2 peptides have specificity ranged from 74%~85%. On the sensitivity, only 9 peptides have 95~100% sensitivity. The other 10 peptides have sensitivity ranged from 27%~94%. Thus, a screening method based on peptide groups was developed for the first time. Taken together, this study described a rapid extraction and detection workflow for widespread β-lactamases, including KPC, IMP, VIM, NDM, OXA, CMY, CTX-M, and TEM, using single colonies of Enterobacteriaceae strains. PRM-targeted proteomics was proven to be a promising approach for the detection of drug-resistant enzymes.